Structural Properties of Epoxy-Silica Barrier Coatings for Corrosion Protection of Reinforcing Steel - Uvida, Mayara Carla [UNESP]; Almeida, Adriana de Araujo [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Hammer, Peter [UNESP] (Mdpi, 2022)
Reinforcement steel extensively applied in civil construction is susceptible to corrosion due to the carbonation process in reinforced concrete and chloride ions diffusion. Epoxy-silica-based coatings are a promising option to guarantee the long-term stability of reinforced concrete structures. In this study, the influence of the proportion between the poly (bisphenol-A-co-epichlorhydrin) resin (DGEBA) and the curing agent diethylenetriamine (DETA) on the structural, morphological, and barrier properties of epoxy-silica nanocomposites were evaluated. To simulate different stages of concrete aging, electrochemical impedance spectroscopy (EIS) assays were performed for coated samples in a 3.5 wt.% NaCl solution (pH 7) and in simulated concrete pore solutions (SCPS), which represent the hydration environment in fresh concrete (SCPS2, pH 14) and after carbonation (SCPS1, pH 8). The results showed that coatings with an intermediate DETA to DGEBA ratio of 0.4, presented the best long-term corrosion protection with a low-frequency impedance modulus of up to 3.8 G omega cm(2) in NaCl and SCPS1 solutions. Small-angle X-ray scattering and atomic force microscopy analysis revealed that the best performance observed for the intermediate DETA proportion is associated with the presence of larger silica nanodomains, which act as a filler in the cross-linked epoxy matrix, thus favoring the formation of an efficient diffusion barrier.
Keywords: Organic-inorganic coating; Sol-gel process; Epoxy-silica; Corrosion protection; Reinforcing steel